Antithrombotic Management for Atrial Fibrillation Patients Undergoing Percutaneous Coronary Intervention or With Acute Coronary Syndrome: An Evidence-Based Update - Zhao, Shujuan; Hong, Xuejiao; Cai, Haixia; Liu, Mingzhou; Li, Bing; Ma, Peizhi (Frontiers in Cardiovascular Medicine, 2021)
Combined antithrombotic regimens for atrial fibrillation (AF) patients with coronary artery disease, particularly for those who have acute coronary syndrome (ACS) and/or are undergoing percutaneous coronary intervention (PCI), presents a great challenge in the real-world clinical scenario. Conventionally, a triple antithrombotic therapy (TAT), which consists of combined oral anticoagulant therapy to prevent systemic embolism or stroke along with dual antiplatelet therapy to prevent coronary arterial thrombosis (CAT), is used. However, TAT has been associated with a significantly increased risk of bleeding. With the emergence of non-vitamin K antagonist oral anticoagulants (NOACs), randomized controlled trials have demonstrated a better risk-to-benefit ratio of dual antithrombotic therapy (DAT) in combination of a NOAC and with a P2Y12 inhibitor than vitamin K antagonist-based TAT. The results of these studies have impacted the recommendations of current international guidelines, which favor a DAT with a NOAC and P2Y12 inhibitor (especially clopidogrel) in this clinical setting. Additionally, aspirin can be administered during the periprocedural period, while the treatment duration of TAT should be as short as possible. In this article, we summarize the up-to-date evidence regarding antithrombotic regimens for AF patients with PCI or ACS, with a specific focus on the optimal approach and critical discussions of key scientific data and future developments for antithrombotic management in these patients.